Implementasi Media Sam’iyyah Basyariyah Dalam Pembelajaran Mufrodhat Wan Nusus Al Masmu’ah Semester Iv PBA IAIMU Pamekasan - Sulaiman, Edy; Isnaini, Anisah (Ulumuna: Jurnal Studi Keilsman, 2021)
The method is a way or means that must be taken to achieve certain goals and of course the sam'iyyah basyariyah media cannot be separated from the use of information technology (IT) or other media which are tools to achieve a learning goal. The application of the sam'iyyah bashariyyah media will make it easier and faster to understand the material (Istima'1 al-Mufrodhat wannusus al-Masmu'ah) for fourth semester students, besides that the learning process is more enjoyable and students are increasingly interested in the material presented, so that learning objectives can be achieved maximally. This type of research is field research using a descriptive qualitative approach. The object of research in this scientific work is the implementation / application of the sam'iyyah basyariyyah media in the istima 'al-mufrodhat wannusus al-masmu'ah semester IV PBA STAIMU Pamekasan course. While the subjects in this study were Arabic language lecturers of PBA STAIMU Pamekasan and fourth semester students of PBA STAIMU Pamekasan. The method used in collecting data is by observation, interview and documentation methods. Based on the results of the data obtained from the tiger-type training in syam'iyyah basyariyyah media with the use of existing technology tools at the time of learning, the steps in applying the sam'iyyah basyariyah media in the form of videos include: (1) preparation before using the media by controlling the location of the media equipment in such a way, (2) Activities while using the media by displaying videos in the form of stories, news and Arabic advertisements (3) follow-up activities by giving some questions during evaluation, and giving oral and written questions to students and the majority of students are able to answer question given. This proves that the use of sam'iyyah basyariyyah media in the form of slides and learning videos is good for application in Arabic learning